التطور التاريخي لرياضة كرة السلة على الكراسي المتحركة للرجال منذ عام 1940م لغاية عام 2002م - عبدالأمير، زينب علي (جامعة بابل - كلية التربية الرياضية, 2012)
اشتمل البحث على أربعة فصول، تضمن الفصل الأول مقدمة البحث وأهميته والتي أوضحت أن دراسة التاريخ ذات أهمية حيوية للمهتمين بمجالات التربية والتعليم بوجه عام، وبمجال التربية البدنية والرياضة بوجه خاص، وذلك لان المواقف المعاصرة والقضايا التي تفرض نفسها في وقتنا الحاضر على المجتمعات ما هي إلا نتاج للماضي، ولذا فإن أي تحليل للحاضر أو تخطيط للمستقبل يستدعي بالضرورة دراسة الأحداث الماضية أي دراسة للماضي. \ ويتضح مما سبق أهمية دراسة التاريخ بوجه عام والتاريخ الرياضي بوجه خاص، على الرغم من ذلك فإن الدراسات التاريخية في المجال الرياضي تعد نادرة جداً، وتاريخ الالعاب الرياضية للمعاقين الأكثر ندرة، بل أن هناك رياضات عديدة لم تتناولها الدراسات التاريخية بالتوثيق والتحليل على حد علم الباحثة، الأمر الذي دفع الباحثة إلى إجراء مثل هذه الدراسة في محاولة منها لتوثيق تاريخ رياضة كرة السلة على الكراسي المتحركة للرجال منذ عام 1940م ولغاية عام 2002م، والمعروفة عالمياً وبارالمبيا، أما مشكلة البحث، فتكمن في التعرف على التطور التاريخي لرياضة كرة السلة على الكراسي المتحركة للرجال، وتوثيق المشاركات والنتائج المتحققة في الدورات البارالمبية والبطولات العالمية والشخصيات المؤثرة فيها، فضلا عن التعرف على التطور التاريخي للاتحاد الدولي لرياضة كرة السلة على الكراسي المتحركة، وذلك في محاولة لإعطاء المعاقين حقهم بحفظ تراثهم وتاريخهم الرياضي، كما اشتمل الفصل الأول على أهداف البحث وهي كالآتي: \ 1- التعرف على التطور التاريخي لرياضة كرة السلة على الكراسي المتحركة للرجال. \ 2- توثيق المشاركات والنتائج المسجلة في الدورات البارالمبية والعالمية. \ 3- التعرف على التطور التاريخي للاتحاد الدولي لرياضة كرة السلة على الكراسي المتحركة. \ واشتمل الفصل الثاني على التطور التاريخي للمسابقات الدولية والدورات البارالمبية لرياضة كرة السلة على الكراسي المتحركة للرجال منذ عام 1940م ولغاية عام 2002م، أما الفصل الثالث اشتمل على التطور التاريخي للاتحاد الدولي لرياضة كرة السلة على الكراسي المتحركة، في حين اشتمل الفصل الرابع على الخاتمة والتوصيات وجاءت أهم التوصيات كالآتي:- \ 1- ضرورة تضمين مناهجنا الدراسية الأكاديمية بتاريخ رياضة المعاقين، من حيث النشأة والتطور التاريخي لمختلف الرياضات الخاصة بهذه الفئات. \ 2- إجراء دراسات مشابهة عن التطور التاريخي لرياضة كرة السلة على الكراسي المتحركة للرجال عربيا ومحليا ومقارنتها بالنتائج العالمية، ورفد المكتبات العراقية بمثل هكذا دراسات لندرتها. \ 3- توعية الباحثين والدارسين بأهمية دراسة تاريخ رياضة المعاقين لإدراك الدور الكبير الذي تلعبه هذه الفئات في رفد الحركة الرياضية بالانجازات الرائعة وقدراتهم الكبيرة في تحدي صعوبات الإعاقة. A search on the four seasons, which included the first chapter Introduction Search and relevance, and that made it clear that the study of history is of vital importance for those interested in the fields of education and education in general, and the field of physical education and sport in particular, because the attitudes of contemporary issues that impose themselves in the present day societies are only the product of the past, and therefore, any analysis of the present or planning for the future necessarily requires the study of past events any study of the past. \ It is clear from the foregoing importance of studying history in general and sports history in particular, however, the historical studies in the field of sports is very rare, and the date of sports for the disabled most scarce, but there are sports many not dealt with historical studies documentation and analysis to the knowledge of the researcher, which prompted the researcher to conduct such a study in an attempt to document the history of basketball on wheelchairs for men since 1940, until 2002, and the internationally renowned Paralympics, the research problem, lies in identifying the historical evolution of the sport of basketball on wheelchairs for men, and documenting Posts and results in courses Paralympics and World Championships and influential figures in, as well as to identify the historical development of the International Federation of Sports basketball wheelchairs, and in an attempt to give the disabled the right to save their heritage and history Sports, also included the first chapter on the objectives of the research are as follows: \ 1- Get on the historical development of the sport of basketball on wheelchairs for men. 2-Documented and the results recorded in the sessions and Paralympics World. 3- Get the historical development of the International Federation for the sport of basketball on wheelchairs. \ And included the second quarter on the historical development of competitions and international courses Paralympics Sports Basketball on wheelchairs for men since 1940, until 2002, Chapter III included the historical development of the International Federation of Sports basketball wheelchairs, while included the fourth quarter on the conclusion and recommendations came the most important recommendations as follows: \ 1- The need to include in our academic curricula on sports for the disabled, in terms of origin and historical evolution of the various sports for these categories. 2- Conducting similar studies for the historical development of the sport of basketball on wheelchairs for men regionally and locally and comparing the global results, and advancing Iraqi libraries such Thus studies of their rarity. \ 3- Educate researchers and students of the importance of studying the history of sports for the disabled to realize the significant role played by these groups in supporting the sports movement remarkable achievements and abilities big difficulties in challenging disability.
Keywords: كرة السلة -- الألعاب الرياضية -- رياضة المعوقين